Multisectoral contributions to health security and formal policy availability at the community level in Nigeria - Enyi Etiaba; Enyi Etiaba; Prince Agwu; Prince Agwu; Prince Agwu; Lesong Conteh; Obinna Onwujekwe; Obinna Onwujekwe (Frontiers in Public Health)
IntroductionMultisectoral plans and actions at the community level are one of the strategies that are deployed in the primary healthcare (PHC) system for improving the health and wellbeing of the people and also a means of addressing the social determinants of health. Multisectoral actions are also a means of implementing the Health in All Policies (HiAP) policy directions, which Nigeria has agreed to implement. However, there is a paucity of knowledge on the level of multisectoral involvement to ensure health security and promotion at the community level. This paper provides new knowledge on what multisectoral activities for health are undertaken at the community level and what can be done to strengthen them towards achieving universal health coverage in Nigeria. It elaborates on previous and current levels of multisectoral collaboration (MSC) activities for health at the community level.MethodsA qualitative cross-sectional case study of three contextually different states in northern (Kano) and southern (Akwa Ibom and Anambra) states in Nigeria. Conceptually, the study was guided by the Expanded Health Systems framework, which recognises potential combinations of collaborations between the non-health sector and other societal partnerships (CSOs, NGOs, community groups, and informal health providers) to directly contribute to community health or indirectly through one or more social determinants of health. The study was also guided by the WHO PHC operational framework, which proposes multisectoral action as one of three key approaches to UHC. Data were collected and triangulated through 103 in-depth interviews with policymakers (health and non-health sectors), formal and informal health providers, and community leaders; 12 focus group discussions with community members (service users) and a review of health and non-health sector policy documents. Thematic data analysis was undertaken.ResultsSeveral community and household-level activities were identified as having been borne out of multisectoral actions. Most activities were initiated by health sector stakeholders in health, whereas others were initiated by non-health sectors (education, environment, agriculture, security, women affairs, social welfare, nutrition, water, sanitation, and hygiene—WASH) or communities. The multisectoral activities contributed to primary healthcare activities and the health security of communities, directly or indirectly, through improving one or several social determinants of health (water supply, housing, environment, security, food, and nutrition). However, most activities, which involved collaborative engagements with non-health sectors, were not backed by any formal, explicit non-health sectoral policies or guidelines. Rather, they were organically initiated and developed to support health security. The support of community leaders and groups facilitated the initiation and sustenance of multisectoral activities, whilst inadequate formal policy backing and funding were the major constraints. Although there are calls in the country for non-health sectors to mainstream health in their sectors, there is yet no clearly established framework or guidelines through which this can be implemented and sustained. A multisectoral action plan for non-communicable diseases has been developed but has not been implemented and evaluated.ConclusionMultisectoral collaboration for health at the community level is important for harnessing resources from outside the health sector that will be used to enhance the health security of communities. Such MSC is potentially a powerful tool for strengthening primary healthcare, towards UHC, and achieving SDG3, as shown by our findings. However, entrenched and sustained MSC should be undertaken through explicitly intentional policy reforms and their implementation through identifying, promoting, and financing MSC actions.